Rho Kinase Inhibition Blunts Lesion Development and Hemorrhage in Murine Models of Aggressive Pdcd10/Ccm3 Disease. Issue 3 (March 2019) - Shenkar, Robert; Peiper, Amy; Pardo, Heidy; Moore, Thomas; Lightle, Rhonda; Girard, Romuald; Hobson, Nicholas; Polster, Sean P.; Koskimäki, Janne; Zhang, Dongdong; Lyne, Seán B.; Cao, Ying; et al.
Abstract : Background and Purpose—: Previously, murine models Krit1 +/− Msh2 −/ − and Ccm2 +/ − Trp53 −/ − showed a reduction or no effect on cerebral cavernous malformation (CCM) burden and favorable effects on lesional hemorrhage by the robust Rock (Rho-associated protein kinase) inhibitor fasudil and by simvastatin (a weak pleiotropic inhibitor of Rock). Herein, we concurrently investigated treatment of the more aggressive Pdcd10/Ccm3 model with fasudil, simvastatin, and higher dose atorvastatin to determined effectiveness of Rock inhibition. Methods—: The murine models, Pdcd10 +/ − Trp53 −/ − and Pdcd10 +/ − Msh2 −/ −, were contemporaneously treated from weaning to 5 months of age with fasudil (100 mg/kg per day in drinking water, n=9), simvastatin (40 mg/kg per day in chow, n=11), atorvastatin (80 mg/kg per day in chow, n=10), or with placebo (n=16). We assessed CCM volume in mouse brains by microcomputed tomography. Lesion burden was calculated as lesion volume normalized to total brain volume. We analyzed chronic hemorrhage in CCM lesions by quantitative intensity of Perls staining in brain sections. Results—: The Pdcd10 +/ − Trp53 −/ − /Msh2 −/ − models showed a mean CCM lesion burden per mouse reduction from 0.0091 in placebos to 0.0042 ( P =0.027) by fasudil, and to 0.0047 ( P =0.025) by atorvastatin treatment, but was not changed significantly by simvastatin. Hemorrhage intensity per brain was commensurately decreased by Rock inhibition. Conclusions—: These results support the exploration of proof of concept effect of high-dose atorvastatin on human CCM disease for potential therapeutic testing. Abstract : Supplemental Digital Content is available in the text.